Evidence in nursing leadership development through action research: an integrative review - Bárbara Souza Rocha; Denize Bouttelet Munari; Luana Cássia Miranda Ribeiro; Lara Gomes Rego (Universidade Federal de Goias, 2017)
This study's goal was to identify evidence of the effects of using action research in nursing leadership development. This is an integrative review of the literature conducted in 2016, guided by the descriptors action research and nursing, which included a total of eight articles. Most studies were conducted in the hospital context, including descriptive qualitative studies whose objective was to analyze the process of changes in the practice of nurses. Regarding the evidence in nursing leadership development, the articles indicated the importance of a shared decision-making process as a critical skill for leadership. The joint construction of management tools proved to be essential to support changes in practice, especially regarding the continuity and maintenance of qualification of leadership professionals.